PENGARUH PERMAINAN KASTI TERHADAP LARI SPRINT 40 M SISWA KELAS V SDN 2 MUARA RUPIT - Khairul Saleh; Deka Ismi Mori Saputra; Iri Hamzah; Rita Zunarti; Apdoludin Apdoludin; Yuliani Puspita Sari (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2023)
ABSTRACT This research is motivated by the low ability of students in running, especially in the 40M sprint learning lesson. The purpose of this classroom action research is to see the effect of baseball on the 40M sprint for fifth grade students at SDN 2 Muara Rupit. The method in this study is a quasi-experimental design or quasi-experimental, with one group pretest and posttest design. The population of this study was 229 students and the sampling technique was purposive sampling, the sample of this study was the fifth grade students of SDN 2 Muara Rupit. totaling 25, 10 women and 15 sons. The instrument used was the 40M running test. The data analysis technique of this research used t-test with a significant level of 0.05. The results showed that there was a significant effect between baseball game training on the 40M sprint run for fifth grade students at SDN 2 Muara Rupit. The results of the t-test obtained the value of tcount=12.10 while ttable=2.06 with a significance level of 0.05. these results show that tcount is greater than ttable. Then Ha is accepted and Ho is rejected if Ha is accepted. Keywords: Sprint, 40 Meter, Game, Kasti.